A brief history of Malawi's: Social Cash Transfer Programme (SCTP) - Pedro Lara de Arruda (International Policy Centre for Inclusive Growth (IPC-IG), 2018)
Malawi is a low-income, landlocked country in Southern Africa with a population estimated at 17.2 million in 2015. The country is divided into 28 administrative districts. Over three quarters (83.7 per cent) of Malawians live in rural areas, and 50.1 per cent of the total population are female. The country is predominantly young, with 45.1 per cent of its population being 14 years old or under, while 51.4 per cent of the population are of working age (15-64 years old). Nearly two thirds (63.5 per cent) of the people aged 15+ participate in the labour force. The overall unemployment rate is 7.5 per cent, while the youth (15-24 years old) unemployment rate is 13.8 per cent (World Bank Open Data 2018). [...]
Keywords: 330; brief; history; Malawi; Social; Cash Transfer; Programme; SCTP